Association between Thyroiditis and Multifocality in Papillary Thyroid Carcinoma - Dedivitis,Rogério Aparecido (2021)
Abstract Introduction Hashimoto thyroiditis (HT) shares many characteristics with papillary thyroid carcinoma (PTC), and some studies show that, when associated, PTC is diagnosed mostly with smaller lesions and multifocal pattern. Objective To evaluate the relationship between HT and PTC. Methods A retrospective study of 155 patients who underwent total thyroidectomy from 2009 to 2015. Demographical, clinical and ultrasonographical data, as well as anatomopathological findings were evaluated. Results There were signs of thyroidits in 35 patients, and 114 patients had a unifocal disease. There was no statistical significance between the variables studied and thyroiditis. However, when compared with the occurrence of unifocal or multifocal lesions, there was statistical significance regarding age (p = 0.038) and mass (p = 0.031). There was no direct relationship between thyroiditis and multifocality (p = 0.325) nor between thyroiditis and cervical extension of the disease (p = 0.300 e p = 0.434). Conclusion There was no relationship between thyroiditis and multifocality in cases of PTC.